Residential Segregation: Concepts, Mechanisms and Effects of Spatial Inequalities - De Falco, Antonio (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Over the past few years, there has been increasing interest in studying the distribution and separation of social groups within urban areas, driven by growing inequalities in social and spatial domains in European cities. This phenomenon is known in the literature as residential segregation and refers to the physical separation of two or more social groups in urban spaces. While residential segregation may not necessarily be problematic, it can pose a significant threat to the social inclusion of disadvantaged groups and exacerbate social inequalities. This is because the social composition of the areas of residence, together with the unequal spatial distribution of services and resources, contribute to defining the structure of constraints and opportunities for individuals, fueling the reproduction, and even the intergenerational transmission of inequalities. This paper aims to explore the sociological definition of residential segregation, the evolution of its study in social sciences, and its multidimensional nature, including the factors contributing to its formation and the different socio-spatial configurations it can assume in urban areas. Particularly, it highlights the role of contextual factors in determining spatial divisions in Western cities, and how residential segregation affects individuals and families in terms of social outcomes and life opportunities. In addition, the paper offers an in-depth focus on the city of Liverpool in England, which can serve as an informative case study to examine how the socio-economic transformations that have affected the city in recent decades, related to the decline of Fordist industry and the process of tertiarisation of the economy, have impacted its socio-spatial configuration. The results of the analysis, based on the latest census data available in the UK (2021), may offer interesting insights for future research, particularly in understanding the dynamics of residential segregation in European cities.